ANALISIS TRANSFORMASI STRUKTURAL EKONOMI DI KOTA PEKANBARU - Sisca Vaulina; Septina Elida (UIR Press, 2014)
The goals of this research were to know the role of agriculture sector (primary sector) on the economy at Pekanbaru city and recognize structural transformation occurred at Pekanbaru city during 1992, 2002, and 2012. The method used case study and secondary data used was PDRB during period 1992, 2002, and 2012.The location quotient (LQ) and shift share were used for data analyses.The results showed that value LQ analysis that is primary sector in Pekanbaru city ranged from 0.007 to 0.02. Its mean the primary sector was non basis sector, the sector has not been able to make export and could notbe able to meet a need and demand of average consumption in the region. The structural transformation occurred at Pekanbaru city were the primary sector (1.26%), the secondary sector(26.47%) and the tertiary sector (72.00%).